2021
DOI: 10.6007/ijarbss/v11-i11/11653
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptual Framework of Housing Purchase Decision-Making Process

Abstract: Buying a housing property is exciting because it marks the beginning of a whole new chapter. Before start looking for a house, it is very important to understand the intention of buying a housing property, whether it is as an investment or for self-occupation. This will affect the type of property to be purchased, whether it is a landed property or a high-rise building. Many potential homebuyers, especially first-time homebuyers, make buying mistakes for the wrong reasons, which makes the process of trying to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Therefore, the intention to purchase is an antecedent to a purchase decision. Research studies (Hassan et al, 2021;Tan & Goh, 2018) found that the decision related to purchase real estate has a link between the "intention to purchase" and "decision to purchase" of customers.…”
Section: Purchase Intentionmentioning
confidence: 99%
“…Therefore, the intention to purchase is an antecedent to a purchase decision. Research studies (Hassan et al, 2021;Tan & Goh, 2018) found that the decision related to purchase real estate has a link between the "intention to purchase" and "decision to purchase" of customers.…”
Section: Purchase Intentionmentioning
confidence: 99%
“…A five-step process of buying decision was identified: identify needs, seek information, evaluate alternatives, purchase decisions and attitudes after purchase (Kotler and Keller, 2005). Hassan et al (2021) developed a conceptual framework for housing purchase decision-making process consisting of housing purchase intention, IJHMA 17,2 housing purchase preferences and purchase decision. Stanton (1994) established a consumer buying decision process that describes social, psychological and situational functions, namely, when and where to buy will affect a purchase decision.…”
Section: Literature Reviewmentioning
confidence: 99%